Methods of Nitriles Synthesis from Amines through Oxidative Dehydrogenation. Issue 19 (24th August 2020) - Patil, Rajendra D.; Gupta, Maneesh Kumar
Abstract: In recent years, oxidative dehydrogenation (ODH) of amines has proven to be an efficient, clean and fundamental route for the synthesis of nitriles. This review focuses on the different types of reactions for the oxidation of amines to nitriles such as transition metal‐catalysis, photoactivation, acceptorless dehydrogenation, nitroxyl radical‐mediated, and N, O‐doped mesoporous carbon. Emphasis is placed on the ODH of amines to the corresponding nitriles using ruthenium catalysts. Metal free systems utilizing iodine, TEMPO and its derivatives, TCCA with or without additives are also discussed. The ODH of amines using N, O‐doped mesoporous carbon is elaborated. Attention is also given to major improvements, achievements, and challenges that still remain in the field of nitrile synthesis from amines. Abstract :